A Brief Semantic Analysis on The Form and Function of Biak’s article ’ma’ - Alfons Arsai; Suardi Sahid (Institut Agama Islam Negeri Palopo, 2022)
Biak language, spoken by 50.000 to 70.000 native speakers, belongs to the West New Guinea subgroup of the Austronesian language family and is spoken in West Papua (formerly known as Irian Jaya), Indonesia, which is found in the northern part of the Geelvink Bay. The typology of this language is SVO and has an agglutinative pattern in which the nouns are simple.This article aims to discuss the semantic function of particle ma in Biak language and to describe its form. The technique used to analyze the data is descriptive approach namely describing the data based on what people actually say by applying the morphological paradigm to see potential morpheme by morpheme in order to determine form, function, and meaning. By doing so, this approach helps to classify which morpheme in the morphological process that the particle ma is inflected or not inflected to in the verbs or other word categories. The finding of this study shows that there are eight semantic functions which are indicated by the particle ma which has different meanings such as to show desire or volition, conjunction, reveal future condition, state reflexive pronoun, to derive verb into noun in morphological process of word formation, tense and mood, adverbial conjunction and phrasal verbs. Morphologically, there are two types of the morphemes in which the particle ma is attached to and is not attached namely as bound and free morphemes.